The Effect of Educational Interventions on Sexual Behavior and Reproductive Health of Women: A Systematic Review - Kohansal, Fereshteh; Nourizadeh, Roghaiyeh; attarzadeh Jahdi, Niloofar S; Mehrabi, Esmat; Arab Bafrani, Mahdie (Advances in Nursing & Midwifery, 2022)
Abstract Introduction: Reproductive and sexual health and its dimensions are important aspects of health in human life and the World Health Organization emphasizes to promote these section health indexes. Since a review study has not been conducted to identify an appropriate approach for intervention in this field. Therefore, this study was conducted with the aim of systematically reviewing the impact of educational and counseling interventions on sexual function of women. Methods: A comprehensive electronic search was carried out with no time limit until 6 August 2022. All published studies with inclusion criteria by 2021 were searched in Embase, Cochrane library, Web of Sciences, Google Scholar, Pubmed, Scopus, SID, and Magiran. The literature search was performed using PRISMA instructions. Cochrane Quality Assessment Scale [adapted for evaluating RCT, interventional studies] was used to evaluate the quality of the articles. Results: From a total of 93 articles obtained from the search in databases, by removing duplicate titles and checking the titles and summaries of the articles, 40 articles were obtained, and finally, after the final review of the full text of the articles, 21 articles were included in the present review. Due to the variety of interventional types in the studies, it was not possible to categorize counseling approaches. Studies showed that interventions based on sexual education and counseling were effective on the outcomes including marital satisfaction, sexual knowledge, sexual satisfaction, marital relationship quality and sexual performance. Conclusions: Designing a comprehensive educational program with an appropriate approach focusing on various aspects of reproductive and sexual health can be an important role in promoting sexual and reproductive health. Therefore, interventional studies are necessary to identify an appropriate intervention approach to enhance reproductive and sexual literacy of couples.